VERIFIKASI PARTAI POLITIK PESERTA PEMILU DI KPU KABUPATEN KERINCI TAHUN 2024 - Amri, Faisal (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2023)
The General Elections Commission as an institution given a mandate based on realizing people's sovereignty, holding general elections, to elect regional heads and people's representatives in the legislature. The purpose of this writing is to know and analyze in depth the function of the general election commission in determining the verification of political parties participating in elections. For this reason, this research was carried out using a conceptual approach, a statutory approach, a historical approach and a case approach. The results showed that the election results issued by the KPU are included in the category of state administrative decisions because they meet the elements of a decision of state administrative officials such as the KPU as an institution authorized to decide election results based on their duties and functions in holding general elections based on the provisions of laws and regulations and the code of ethics for election organizers. The decision on the election results issued by the election commission is concrete in nature, setting it clearly. The decision has legal consequences for a person or civil law entity involved in conducting elections. The process of ratifying and determining general election decisions is not only based solely on the decision-making mechanism within the KPU institution itself but has been preceded by the process of holding elections in accordance with laws and regulations